SEISMIC DESIGN OF SINGLE SPAN STEEL GIRDER BRIDGES AND BRIDGES IN SEISMIC PERFORMANCE CATEGORY A (Journal of Engineering, 2010)
This paper studies the validity and accuracy of the seismic design force recommended by AASHTO for single span bridges. A parametric study for single steel girder bridges is presented, included the effect of span length and elastomeric bearing and lateral bracing (cross-frame) stiffness. The results of simplified AASHTO method are compared with response spectrum and time history analysis. Also studying the seismic design reqiurements for continuous steel girder bridges in seismic performance category (A), included the effect of span length, seismic zone, effect of elastomeric bearing and cross-frame stiffness and bridge skew on their seismic responses. It is concluded that the AASHTO simplified analysis method for single span bridges underestimates the seismically induced forces at supports and the proposed seismic design force of (2.5 multiplied by acceleration coefficient multiplied by tributary weight w(x)) has been recommended for single span bridges for seismic zone 3 and 4 and for soil type II. Also it is observed that the seismic design force for two span continuous bridges in performance category A is safe and conservative method to predict the shear forces transferred by connection elements to the substructures.